Cation Tuning of Supramolecular Gel Properties: A New Paradigm for Sustained Drug Delivery. Issue 13 (2nd February 2017) - Ramin, Michael A.; Sindhu, Kotagudda Ranganath; Appavoo, Ananda; Oumzil, Khalid; Grinstaff, Mark W.; Chassande, Olivier; Barthélémy, Philippe
Abstract : Hydrogels formed by the self‐assembly of low‐molecular‐weight gelators (LMWGs) are promising scaffolds for drug‐delivery applications. A new biocompatible hydrogel, resulting from the self‐assembly of nucleotide‐lipid salts can be safely injected in vivo. The resulting hydrogel provides sustained‐release of protein for more than a week.